Indoor and outdoor radon measurements at lung cancer patients' homes in the dwellings of Rize Province in Turkey - Akbulut Özen, Songül; Celik, Necati; Dursun, Emrehan; Taskin, Halim (Springer, 2018)
In this study, indoor and outdoor radon (Rn-222) surveys were carried out in the summer and winter seasons in homes of one hundred lung cancer patients in the year 2013-2014. The aim was to investigate the relationship between radon and cancer patients. Lung cancer patients completed a questionnaire concerning their living environment, various physical parameters and living habits. Pearson correlation and t tests revealed no meaningful results between radon concentrations, on one hand, and environmental and personal living habits, on the other hand. Consequently, the BEIR VI model was adapted and Rn-222 exposure was estimated to be responsible for about 12% of the lung cancer incidences in the winter season and around 5% in the summer season in the Rize Province. However, due to the limited number of data and numerous parameters that could lead to lung cancer, the estimations done with the model should be taken very lightly. The annual effective doses due to inhalation of indoor and outdoor Rn-222 were estimated to be, respectively, 1.43 and 0.94 mSv y(-1). The indoor and outdoor annual effective doses were, respectively, close and below the world annual effective dose (1.3 mSv y(-1)). At the district level, the indoor annual effective dose equivalent in the A degrees yidere district was 4.52 mSv y(-1), which was 3.5 times greater than the world average. The number of patients in the majority of the houses in this district was more than one.
Keywords: Radon; Lung cancer; Effective dose; Rize Province